Hydraulic characteristics and vegetation performance of the Yellow River sediment modified by biochar - Baoyong Liu; Mingji Liao; Yong Wan; Xingxing He; Dongli Wang (Biogeotechnics)
The Yellow River sediment (YRS) is an important potential soil resource for the mine land reclamation and ecological restoration in the arid regions of northern China. However, it has the shortcomings of poor water-holding capacity and needs to be modified urgently. Therefore, two types of biochar, namely rice husk biochar (RHB) and coconut shell biochar (CSB), were utilized in this study to modify the YRS and compared with rice husk ash (RHA). Some engineering properties of the modified YRS (MYRS), including pore structure, water retention, permeability, and vegetation performance, were investigated by considering the effects of biochar types and dosages. Results showed that the addition of the three materials decreased the bulk density of the YRS and increased the volume of extremely micro pore (d<0.3 µm), as well as the effective porosity and capillary porosity, thus contributed to an increase in the water-holding capacity of the sediment. Among the three conditioners, RHB is optimal choice for improving the water-holding capacity of YRS. Furthermore, the effect becomes more pronounced with increasing application rates. With the addition of the three materials, the permeability coefficients of MYRS gradually decreased, while the water retention rate during evaporation significantly increased. The pot experiment showed that the three conditioners all had significant promoting effect on the growth of oats. In particular, compared to plain soil, the total biomass of oats grown for 21 days increased by 17.46%, 32.14%, and 49.60% after adding 2%, 4%, and 8% RHB, respectively. This study introduces a new approach for using YRS as planting soil in arid and semi-arid areas of China to facilitate mine ecological restoration.